(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the dynamic landscape of global communication and interconnected societies, the acquisition of language skills plays a pivotal role in shaping the educational journey of secondary school students. The ability to effectively communicate in multiple languages not only broadens cognitive abilities but also fosters cultural understanding and opens doors to diverse opportunities in an ever-evolving world. However, despite the inherent importance of language learning, secondary school students often encounter challenges that hinder their proficiency and confidence in acquiring new languages.